(untitled) (Indian Journal of Animal Production and Management, 2015)
An investigation was carried out in two districts of West Bengal namely Nadia (alluvial) and South 24 Paraganas (coastal) to evaluate the socio-economic status of the goat farmers through survey by a structured questioner amongst the selected beneficiaries by local institution and communities. The study revealed that the average goat holding per house hold was better for female farmers in both the agro climatic regions. The income (11.63 %) generated from goat husbandry in coastal region was less than alluvial region (15.22%). The income generated in coastal and alluvial by the female farmer were Rs. 2375.41±304.49 & Rs. 2900.0± 438.95 better compared to that of the male farmers Rs. 1646.66±426.31 & Rs. 2164.70± 392.19 respectively, in relation to goat husbandry practices in both the regions, providing the women empowerment. Majority of the goat farmers gain information from personal cosmopoliteness in alluvial region, whereas in coastal region, personal localiteness was the main source of information. The overall knowledge level of goat farmers in alluvial region was better compared to that of coastal region. The attitude of farmers towards goat farming due to mass media, personal cosmopoliteness and personal localiteness had significant effect in both the agro-climatic regions.